FROM GENUS VIOLENCE TO INSTITUTIONAL VIOLENCE: TAKING ABOUT VIOLENCE WITH THE PROFESSIONALS/STAFF FROM DP IN FLORIANOPOLIS - Fernando Luiz Salgado da Silva (Extensio: Revista Eletrônica de Extensão, 2009)
These job recommend to expound a intervention done together with the Woman Police Station (6th Precinct) from the municipalite of Florianopolis. The intervention that inicially had the intention to discuss gender and violence between the employees. To implemment a support group to the man whom are the authores of such violence at the station to create different effects in the institution. Whereby in a strange working space deceitful by a vigour field very intuitive. We use in the article concepts that comes from institutional analyses. Where we put these analyses of the vigours fields and the institution that cross these establishments.